The Effect of Soil Coverings on Cellulose Decomposition Activity of Sandy Soil - Varga, Csaba (Acta Agraria Debreceniensis, 2003)
The purpose of our experiments is to discover the effect of different soil cover matter (agroszövet and black polyethylene) on actual (under field circumstances) and potential (under laboratory circumstances) cellulose decomposition activity. In our field research, the Unger-test was used, and in laboratory research, the Petkov-Markova method was applied. In the first year of the experiment (2000) actual cellulose decomposition activity was significantly higher in covered than in the uncovered soil both in spring and autumn. The difference between the two treatments was significant only in spring. In the spring of 2001 black polyethylene showed significantly the lowest, activity, while in autumn the agroszövet (a porous black polyethylene) showed significantly the highest activity. In the autumn of 2001 the soil covered by black polyethylene gave non-significant,and the soil covered by agroszövet gave a significant higher activity value than the control. Averaging the two experimental years (2000-2001), the actual cellulose decomposition activity was significantly higher in covered soils both in spring (with 30-39%) and in autumn (with 34-69%). Moreover, in autumn a significantly higher value was detected under agroszövet than in any other treatment. The difference between the effect of treatments was not significant. In 2000, the potential cellulose decomposition activity was the highest in soil covered by agroszövet in spring, but in autumn higher activity value was detected in every covered soil than in the control. In the spring of 2001, every covered soil showed a lower, but in autumn a higher, potential cellulose decomposition rate than the control. The activity decreased significantly 27 (agroszövet) and 45 (black polyethylene) percent in spring, and increased no- significantly 8 (agroszövet) and 4 (black polyethylene) percent in autumn. During the two experimental years, we observed on average lower potential cellulose decomposition activity (15-60%) in spring and a higher one (14-43%) in autumn. Neither was significant. The dynamic of potential cellulose decomposition activity averaging 2000 and 2001 showed a slight, the actual cellulose decomposition activity an explicit non-significant upward tendency. There was a strong (r=0,189) correlation obtained between the actual and potential cellulose decomposition activity of soil, and a medium-strong (r=0,673) relationship between the soil moisture content and actual cellulose decomposition activity.